INOVASI DAN MODERNISASI KURIKULUM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Qolbiyah, Aini; Mansur, Amril; Bakar, Abu (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to discuss innovation and modernization of curriculum in Islamic religious education learning. Islamic Education as a series of Islamic subjects is delivered either formally in schools or informally and non-formal at home and in the community with materials taught from elementary school to tertiary levels must respond to this “Merdeka Belajar” policy well. This research is a literature study, namely research that is sourced from library materials using a qualitative approach. In this case, the researcher explored a number of data, both primary data and secondary data with the following steps: reading and studying in depth primary data such as books, journals, articles, theses and dissertations related to the discussion of innovation and modernization of curriculum in Islamic religious education learning. The conclusion of this study is that The existence the scope of curriculum of Islamic Religious Education is: 1) Al-Qur'an, 2) Hadith as the words, deeds and things of the Prophet, 3) Fiqh, 4) Aqidah morals, and 5) the history of Islamic culture. The innovation used when learning Islamic Religious Education is to use the Contextual Teaching and Learning (CTL) method or Learning Strategy.